CHANGES IN THE LIPID STATUS AND LIPID PEROXIDATION PROCESSES OF STERLET BREEDERS RAISED AT FARMS - N. A. Abrosimova; S. S. Abrosimov (Юг России: экология, развитие, 2014)
Comparative analysis of lipid parameters, lipid peroxidation processes and antioxidant system in liver and muscles of five-yearold sterlet raised at the sturgeon fish-breeding farm and from the wild population has not revealed any deviations from the physiological norm of the fish. Some minor differences in the parameters studied reflect, possibly, compensatory reactions of the organism to the specific conditions of breeding.